Peningkatan Kemampuan Pemecahan Masalah MatematikaMelalui Strategi Problem Solving Tipe Draw A Picture(Ptk Pembelajaran Matematika Kelas Viii Semester Genap Smp Negeri 2 Kartasura Tahun 2015/2016) - NURLALITA NUGROHO SAFITRI, CHOIRUNISA; , Rita P. Khotimah, S. Si., M. Sc; , Sri Rejeki, M.Pd., M.Sc (2016)
The background of this study is low of problem solving ability of math in class eightth grade of junior high school 2 of Karatasura. The purpose of this study to describe the improvement of junior high school 2 of Karatasura student is problem ability of math by using problem solving type draw a picture strategy. This study belongs to action class research. The technique used for collecting data were observation, testing, field notes, and documentation. The results showed that the improvement of junior high school 2 Karatasura student in solving math problem ability can be seen from 1) understanding the problem, from 11 students (36.67%) to 22 students (73,33%), 2) planning to solve the problem, from 7 students (23.33%) to 18 students (60%) and 3) implementing the planning to solve problems, from 5 students (16.67%) to 15 students (50%). Based on the analysis, it can be concluded that the applying of problem solving type draw a picture strategy can improve math problem solving ability.